Children’s texts prescribed in Zimbabwean high schools as historical narratives: a close study of Hanson’s Takadini, Gascoigne’s Tunzi the Faithful shadow and Chater’s Crossing the boundary fence. - Munyuki, Tanyaradzwa Angela (Midlands State University, 2014)
This research is an examination of the use of Children’s texts prescribed for Zimbabwean Junior high schools as historical narratives. This is an angle which has not been adequately explored as most of the texts in the Zimbabwean junior High curriculum are often valued for their didactic contribution while ignoring their historical value altogether. The research will also attempt to establish what kind of history is being narrated in the texts and whose history it is by examining works by non indigenous Zimbabwean authors, Gascoigne, Chater and Hanson. The inclusions and exclusions of certain events in the literary historical representations will form the inquiry of the study.